LEGAL PARADIGM IN THE DEVELOPMENT OF NATIONAL ECONOMIC PROGRESS - Niken Larasati (Geuthèë Institute, Aceh, 2022)
As a nation, people's lives are controlled by a basic law known as the constitution or constitution, namely the written basic law which is the basis for the movement, basis and orientation of the journey of life. The 1945 Constitution affirms that, Indonesia is a country based on law (reetstaat). This affirmation means that, as a State, Indonesia has chosen the State (wlfarestaat) as the form of the State, which means that, every action and its consequences, which are carried out by all parties in this State, must be based on law and be resolved according to law. To deal with very complex problems, namely to carry out such a central role in development, the law must first have adequate capabilities.